An Introduction to Physical Science, 15th Edition - James Shipman (Cengage Learning, 2020)
Designed specifically for non-science majors and beginning science students, this easy-to-understand text presents the fundamental concepts of the five divisions of physical sciences: physics, chemistry, astronomy, meteorology and geology. The new edition offers new high-interest ""Physical Science Today"" articles featuring timely and relevant applications. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.